Pyrolysis and co-pyrolysis of Laminaria japonica and polypropylene over mesoporous Al-SBA-15 catalyst - Lee, Hyung Won (Springer, 2014)
The catalytic co-pyrolysis of a seaweed biomass, Laminaria japonica, and a typical polymer material, polypropylene, was studied for the first time. A mesoporous material Al-SBA-15 was used as a catalyst. Pyrolysis experiments were conducted using a fixed-bed reactor and pyrolysis gas chromatography/mass spectrometry (Py-GC/MS). BET surface area, N(2) adsorption-desorption isotherms, and NH(3) temperature programmed desorption were measured to examine the catalyst characteristics. When only L. japonica was pyrolyzed, catalytic reforming slightly increased the gas yield and decreased the oil yield. The H(2)O content in bio-oil was increased by catalytic reforming from 42.03 to 50.32 wt% due to the dehydration reaction occurring on the acid sites inside the large pores of Al-SBA-15. Acids, oxygenates, mono-aromatics, poly aromatic hydrocarbons, and phenolics were the main components of the bio-oil obtained from the pyrolysis of L. japonica. Upon catalytic reforming over Al-SBA-15, the main oxygenate species 1,4-anhydro-d-galactitol and 1,5-anhydro-d-manitol were completely removed. When L. japonica was co-pyrolyzed with polypropylene, the H(2)O content in bio-oil was decreased dramatically (8.93 wt% in the case of catalytic co-pyrolysis), contributing to the improvement of the oil quality. A huge increase in the content of gasoline-range and diesel-range hydrocarbons in bio-oil was the most remarkable change that resulted from the co-pyrolysis with polypropylene, suggesting its potential as a transport fuel. The content of mono-aromatics with high economic value was also increased significantly by catalytic co-pyrolysis.